Saúde sexual e reprodutiva: perspectivas e intervenção para adolescentes em escola municipal de Santa Maria, RS - Seady, Daniela Aline Kaufmann (2014)
The situation of the Brazilian reality in health has been constituted to multidetermined phenomena; it has remained important and serious social problems and reproductive health among teenagers. The inopportune pregnancy and Sexually Transmitted Infections (STIs) diseases . These two items show the need to strongly connect the areas of health and education in order to conduct the promotion and health education aimed, in this case, sexual and reproductive health of teenagers. Objective: to analyze the results of operations and the performance of a health professional , as an educator in Teenager Health , especially in sexual and reproductive area , by students of a municipal school in Santa Maria / RS . Methods: exploratory and descriptive research, the type quantity / quality. In school year 2013, 17 meetings / interventions of health professionals of a Family Health Strategy (fortnightly periodicity) with 32 teenagers aged between 12 and 14 years were performed . It has used a participatory methodology and applied a pre and post-test questionnaire and individual interviews. Results and discussion: Project added knowledge about sexual and reproductive health. It was found that the performance of combined actions (health and school) may contribute to the development of more informed and more critically reflective teenagers, especially when it comes to issues of complex approach, not included in the formal curriculum. Working with sensitive issues related to sexual and reproductive health, in a dynamic, honest and participatory approach it can be an efficient strategy to promote behavior change towards sexuality of teenagers. Final Thoughts: through this study, we realized the importance of the implementation of a participatory and continuous education, offered by qualified and licensed personnel working with sexual and reproductive health.